Dakwah Musik: Modernisasi Dakwah Studi Hadroh Riyadhatus Shalihin Pekanbaru - Azizah, Nurul; Pipir Romadi; Pramana, M. Agung (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2024)
In the context of spreading da'wah, there is diversity in spreading it, one of which is da'wah with music. This research was motivated by the use of musical art in spreading da'wah which was used by Hadroh Riyadhatus Shalihin through the poetry he sang. This article examines how da'wah activities use Hadroh art. This article attempts to answer the main question, namely how did Hadroh Riyadhatus Shalihin renew the da'wah movement through music? Meanwhile, the follow-up question that the writer will explore is how were the activities displayed by Hadroh Riyadhatus Shalihin? To answer these questions, the author uses qualitative methods with data collection techniques through observation, interviews and documentation. The research results show that da'wah through music performed by the Hadroh Riyadhatus Shalihin group makes an innovative contribution to modernizing da'wah, as well as contributing positive things to the world of da'wah and the members who are members of Hadroh RiyadhatusShalihin. The form of da'wah carried out by Hadroh Riyadhatus Shalihin is from poetry which contains Islamic teachings and increases love for Allah SWT and prophet.